Multifunctional Role of Integrated Farming System in Developing Countries - Dasgupta, Purnabha; Goswami, Rupak; Ali, Md Nasim; Chakraborty, Somsubhra; Saha, Subhrajit K. (International Journal of Bio-resource and Stress Management, 2015)
Agro-ecological practices, including integration within farming systems, have increasingly been acknowledged as key development alternative to safeguard rural people’s basic needs. It also enhances farmers’ socio-ecological capacities to sustain livelihoods. This paper explores the multidimensional nature of agro-ecological practices and takes stock of its multiple outcomes in smallholder systems of developing countries. Literatures suggest that farmers’ foremost concern is to meet their socio-economic, cultural and ecological needs in addition to combating multiple adversities caused by biotic and abiotic stresses. This asks for planned integration among the components in small farms leading to reduced stress and multiple benefits to the farm households. Integration among the components of farming system are often employed as a livelihood strategy in small farms and it plays a pivotal role in meeting the multidimensional needs of the farm family such as food security, risk reduction, income and employment, biodiversity, carbon storage and energy efficiency in farm. Public extension must appreciate IFS as a socio-ecological intervention, instead of a technology, to achieve varied desirable socio-economic-ecological outcomes.